Pemberdayaan Dendeng Daun Singkong Terhadap Peningkatan UMKM di Kampung Jatidatar Mataram - Alfin Almustajab; Habib Shulton Asnawi; M.Muslih; Ilham Wahyudin; Lailatul Munawaroh; Karismatul Syari’ah; Sari Safitri; Afifah Asma; Indah Saputri; Salma Roidah; Alfina Damayanti; Adi Bimantoro; Nur Hidayati (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2024)
This research discusses community empowerment in the use of cassava leaves to make processed food in the form of beef jerky. This community empowerment was carried out together with the Women's Farming Community in Jatidatar Village, Mataram. This mentoring program aims to enable people to gain skills and theoretical understanding in processing cassava leaves into beef jerky and how to package them into products that have selling value and can market the products that have been produced through social media. Apart from that, by using cassava leaves, the community will get a solution in utilizing the abundant cassava plants and in improving the community's economy. The focus of this article's study is How does empowering cassava leaf jerky increase MSMEs in Jatidatar village, Mataram and product marketing through digital marketing? The service research method or strategy used in this program is the Asset-Based Community Development (ABCD) method. The ABCD method is a community service approach that is oriented towards providing the community with the power to recognize and utilize all the advantages and assets it has for the benefit of the community. The results of this research are that the assisted communities can independently make beef jerky from processed cassava leaves which is nutritious and has sales value. The assisted community can market the products produced through social media and the products from this assistance can be marketed widely so that they can increase MSMEs in Jatidatar Village.